From Shelters to Dwellings The Zaatari Refugee Camp - Dalal, Ayham (Re-Figuration von Räumen, 2022)
In Zaatari camp, Jordan, thousands of Syrian refugees were sheltered in tents and caravans, which they steadily appropriated and turned into dwellings that responded to their social and cultural needs. In this book, Ayham Dalal takes a closer look at this remarkable transformation. He draws on the tension between 'the shelter' and 'the dwelling' to unravel how new spaces unfold in between them, where refugees become architects and the camp is dismantled and reassembled. From Shelters to Dwellings is the first study to uniquely combine ethnographic observations with new architectural research methods, to illustrate in detail how refugees inhabit shelters. It is a must-read for anyone interested in understanding how camps and shelters are transformed by the powerful act of dwelling.